2011
DOI: 10.3109/14767058.2011.599081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resveratrol on blood pressure in a rat model of preeclampsia

Abstract: The present study demonstrated that resveratrol did not decrease blood pressure, and did not result in a significant response in blood flows and placental pathology parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Due to its natural and safe origin, the use of RESV has been reported in complications during pregnancy (22), including gestational diabetes mellitus (23). Of particular interest to our current study, the anti-hypertension property of RESV has also been demonstrated in a number of studies employing both animal and clinical studies (13, 14, 15, 16, 17). Given its widely reported anti-hypertensive function, we therefore also employed RESV in the current clinical trial among pregnant women affected by PE, with the hypothesis that RESV could also exhibit benefits in relieving hypertension in pregnancy-induced PE.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Due to its natural and safe origin, the use of RESV has been reported in complications during pregnancy (22), including gestational diabetes mellitus (23). Of particular interest to our current study, the anti-hypertension property of RESV has also been demonstrated in a number of studies employing both animal and clinical studies (13, 14, 15, 16, 17). Given its widely reported anti-hypertensive function, we therefore also employed RESV in the current clinical trial among pregnant women affected by PE, with the hypothesis that RESV could also exhibit benefits in relieving hypertension in pregnancy-induced PE.…”
Section: Discussionmentioning
confidence: 85%
“…For instance, in rat model of PE, RESV was reported to reduce blood pressure (13), as well as inhibit trophoblast apoptosis through oxidative stress (14). In a pregnant mouse model with reduced blood supply to the uterus, RESV increased uterine artery blood flow velocity and fetal weight (15).…”
Section: Introductionmentioning
confidence: 99%
“…The following food groups and food extracts have high AMPKactivating capacity: resveratrol (red grape skin extract) [114][115][116][117][118], nootkatone (grapefruit extract) [119], ajoene (garlic extract) [120], BDIM (cruciferous vegetable extract) [19,121], and many others [122]. Medicines activate AMPK including Asa [16], Met [35], phenformin [123,124], rosiglitazone, and phenobarbital [125,126], and there may be others.…”
Section: Discussionmentioning
confidence: 99%
“…13 Green tea supplements are also reported to reduce blood pressure in healthy humans, 14 insulin-resistant adults 15 and in subjects with pre-hypertension. 16 Resveratrol, a polyphenol found in grape skin, lowers arterial pressure in hypertensive 17,18 and obese rat models. 19 Quercetin, a flavonol found in onions and apples, can also alleviate hypertension in pressure-overloaded rats 20 and spontaneously hypertensive rats.…”
Section: Introductionmentioning
confidence: 99%